Advanced monitoring system of sinter plant. (July 2015) - Vannocci, M.; Colla, V.; Pulito, P.; Saccone, M.; Zagaria, M.; Dimastromatteo, V.
<x content-type="archive" xml:space="preserve">Abstract</x> A correct management of the sinter plant is crucial for the productivity of an integrated steelwork, as the sinter quality has a direct and considerable impact of the blast furnace productivity and efficiency. To this aim, it is of utmost importance to continuously monitor the sintering process in order to preserve its stability as well as the homogeneity of the combustion along the entire length of the sinter bed. In particular, the permeability of the sinter mix once it lays on the strand is a crucial factor to monitor in the different areas of the bed together with the temperature distribution on the final part of the strand, just before the material discharge in the crusher. The charging gates, on the other hand, are the most natural mean to affect permeability itself, as their opening levels affect the distribution of the material on the strand. Here an innovative monitoring system is presented, which have been installed and tested at ILVA Taranto Works and integrates a series of measuring devices distributed on different zones of the machine. All the information collected by the sensing system is jointly exploited in order to obtain a clear and updated picture of the ongoing process, by providing a valuable support to plant engineers and technicians managing the sinter machine both for standard operations and for programming maintenance interventions.